The Influence of Public Participation on the Performance of the Regional Council (DPRD) in Decision-Making: (Study of the Sumenep Regency DPRD) - Moh. Fendi; Rachmad Hidayat (Universitas KH. Abdul Chalim Mojokerto, 2026)
Public participation in public decision-making plays a crucial role in building a democratic foundation. Public participation is not merely a decorative element, but a key element that ensures that the resulting policies and decisions reflect the needs and aspirations of the community as a whole. This study aims to determine the effect of public participation on the performance of the Regional People's Representative Council (DPRD) in decision-making. This research is quantitative. The sample used in this study was 68 respondents. The sampling technique used in this study was a non-probability sampling method with a lameshow method. This research was conducted among the public. The analysis used multiple linear regression analysis to examine the influence between variables in several stages. The results show that public participation has a partial and significant effect on the performance of the DPRD in decision-making.